Síntese de compostos contendo N-heterociclos de 5 membros e avaliação da atividade biológica frente a NS3 Helicase do vírus Zika - Vidal, Hérika Danielle Almeida (2024)
Epidemiological and biological studies have shown that Zika virus (ZIKV) infection is strongly associated with neonatal microcephaly and Guillain-Barré syndrome in adults. To date, there is no vaccine and/or efficient drug that can control this virus. A promising, but little explored, target in drug discovery against ZIKV is the non-structural protein 3 (NS3). In this work, fragment-based drug discovery using high-throughput screening (HTS) experiments showed that a hydantoin derivative and an oxadiazole derivative were located at RNA site and therefore considered promising as ligands of the ZIKV NS3 helicase. Based on these results, compounds containing hydantoin and/or oxadiazole were synthesized. Among the various methods used are multicomponent reactions (MCR), such as the Ugi-split reaction, which offer a sustainable approach and allow for broad structural variability. Coupling reagents, such as TBTU, HATU and Mukaiyama, were also used for amide and ester formation reactions. Bioisosteric substitutions of oxadiazole with piperazine and triazole, obtained through the copper-catalyzed azido-alkyne cycloaddition reaction, were also explored. In parallel, the synthesis of highly substituted δ-lactams was studied in a one-pot reaction, through intramolecular Michael addition of Ugi products. Despite the limitations, the method presents a versatile and easy-to-manipulate approach that guides the precepts of Green Chemistry. Regarding biological evaluation, it was possible to demonstrate, through thermal and in vitro tests, that the proposed N-heterocycle derivatives are promising for the development of drugs that can act against ZIKV.